Mitochondria of transformed cell as a target of antitumor influence - E. M. Frantsiyants; I. V. Neskubina; E. A. Sheiko (Исследования и практика в медицине, 2020)
Mitochondria are intracellular organelles in eukaryotic cells that participate in bioenergy metabolism and cell homeostasis, including ATP generation through electron transport and oxidative phosphorylation in combination with oxidation of metabolites by the tricarboxylic acid cycle and fatty acid catabolism via β-oxidation. the production of reactive oxygen species, as well as the initiation and implementation of apoptosis. Mitochondria play a crucial role in cellular energy metabolism and the regulation of programmed cell death. mitochondria activate numerous signaling pathways associated with cell death. Mitochondria have the ability to control the activation of programmed cell death by regulating the translocation of proapoptotic proteins from the intermediate space of mitochondria to the cytosol. This is the reason for the emergence of a new discipline — mitochondrial medicine. The review examined and analyzed scientific publications on the role of mitochondria in the life support of transformed cells, the study of their functioning and structurally functional dysfunctions, as part of mitochondrial medicine. Mitochondrial medicine is a developing discipline whose significance stems from the central function of mitochondria in the production of adenosine triphosphate, the generation of reactive oxygen species, and cell death due to necrosis or apoptosis. Consequently, mitochondrial dysfunction plays an important role in the pathophysiology of cancer, many other common diseases and side effects of drugs. Perhaps the combined use of modulators of mitochondrial metabolism and antitumor therapy will contribute to the emergence of a new direction in antitumor treatment, which will significantly increase the effectiveness of cancer treatment.